Implementation of asymmetric processing on multi core processors to implement IOT applications on GNU/Linux framework - Jain. S, Poonam; S, Pooja; Roy. K, Sripath; K, Abhilash; B V, Arvind (International Journal of Engineering and Technology, 2018)
Internet of Things brought in a bigger computing challenges where there came a need for running tasks in a multi-sensor and large data processing is involved. In order to implement this requirement multiprocessors are being used for implementation of IoT Gateways. There comes a need for specific tasks having a resource dedicated for its job. To fulfill this we face a hurdle in choosing dedicated processor or shared processor in a Symmetric Processing Architecture. Dedicated processor are the one in which all the tasks are being processed on a single core where as in fair share processors specific processes are assigned to specific cores. Symmetric processing makes use of dedicated processors where as Asymmetric processor makes use of shared processors. Asymmetric Multi Processing can be used in real time applications in order to solve real time problems, one such platform is IOT. In this paper we have evaluated Asymmetric processing on GNU/Linux Platform to test multiple threads running on different multi-core processors architectures to realize the same for running IOT applications having higher computational requirements in the future.Â
Keywords: Asymmetric Multiprocessing; GNU/Linux; Internet of Things; Scheduling; Symmetric Multiprocessing